No basalt accumulation and segregation atop the 660-km discontinuity beneath the Sea of Okhotsk - BingXin Zhou; XiaoBo He (Earth and Planetary Physics, 2024)
Recent seismic evidence shows that basalt accumulation is widespread in the mantle transition zone (MTZ), yet its ubiquity or sporadic nature remains uncertain. To investigate this phenomenon further, we characterized the velocity structure across the 660-km discontinuity that separates the upper mantle from the lower mantle beneath the Sea of Okhotsk by modeling the waveform of the S660P phase, a downgoing S wave converting into a P wave at the 660-km interface. These waves were excited by two regional >410-km-deep events and were recorded by stations in central Asia. Our findings showed no need to introduce velocity anomalies at the base of the MTZ to explain the S660P waveforms because the IASP91 model adequately reproduced the waveforms. This finding indicates that the basalt accumulation has not affected the bottom of the MTZ in the study area. Instead, this discontinuity is primarily controlled by temperature or water content variations, or both. Thus, we argue that the basalt accumulation at the base of the MTZ is sporadic, not ubiquitous, reflecting its heterogeneous distribution.